Uma arquitetura modular para controle de FMS - Martins, Ricardo Wagner Campos (Universidade Federal de São Carlos, 2005)
In order to attend the market quickly, a company need to have flexibility and to change its production line, to assist to the production of personalized products, to change the raw material or, even, the conception of the product like in an automatic system of manufacture. Administration of processes, industrial automation and IT (Information Technology) are essential to guarantee not only the companies, competitiveness but their survival inside of this scenery. The larger interest among the automatic systems of manufacture in this work is the flexible manufacture system (FMS), for its inclusion and complexity and, consequently, its control and the variety of architectures, as the centralized, the hierarchical, the heterarchical, the hybrid and, finally the multi - agent, therefore the main focus of this work will be the control system of a FMS. So one of the architecture alternatives, is the proposal using a system of hybrid control, because it allows the communication among levels, by sidelong, and the modules involved in the production process and factory ground control, so it will be possible, to determine which are the instances or moments so of decision, describing the used functions, as well as the treated information. To make possible the modeling modules are used: manager, selective and movement controller facilitating the construction of a structured algorithm aiming at the detail of the process mapping of communication about the actions unchained in the factory ground.
A modular architecture for control of FMS
Keywords: Sistemas especialistas (Computação); Sistemas flexíveis de fabricação; Arquitetura de controle; Control architecture; Flexible manufacturing systems; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO